The Land of mystery in the South [videorecording] - Kim Yang Rae; Lee Hongki; Moon Ye Won (Timeless journey)
A journey to the southwest Korean peninsula. Explores the national treasures of museums, ancient dynasties temples, sculpture parks, origins of Korean art and culinary culture. Discusses also the customs and culture of the Koreans.